2020
DOI: 10.1111/cas.14356
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐375‐3p enhances chemosensitivity to 5‐fluorouracil by targeting thymidylate synthase in colorectal cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractResistance to chemotherapy is a major challenge for the treatment of patients with colorectal cancer (CRC). Previous studies have found that microRNAs (miRNAs) play key roles in drug resistance; however, the role of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 51 publications
0
53
0
Order By: Relevance
“…At present, a large number of studies have shown that, in addition to mRNAs, non-coding RNAs also related to drug resistance of cancers, including gastric cancer [33], bladder cancer [34], lung adenocarcinoma [35]. Moreover, in CRC drug resistance studies, it was reported that LINC00957 could increase 5uorouracil resistance and result in poor survival of patients [36], hsa_circ_0079662 was related to oxaliplatin resistance via TNF-α pathway [25], microRNA-375-3p was involved in 5-uorouracil resistance by targeting thymidylate synthase [37].…”
Section: Discussionmentioning
confidence: 99%
“…At present, a large number of studies have shown that, in addition to mRNAs, non-coding RNAs also related to drug resistance of cancers, including gastric cancer [33], bladder cancer [34], lung adenocarcinoma [35]. Moreover, in CRC drug resistance studies, it was reported that LINC00957 could increase 5uorouracil resistance and result in poor survival of patients [36], hsa_circ_0079662 was related to oxaliplatin resistance via TNF-α pathway [25], microRNA-375-3p was involved in 5-uorouracil resistance by targeting thymidylate synthase [37].…”
Section: Discussionmentioning
confidence: 99%
“…5-FU is a uracil analog that inhibits thymidylate synthase, which is the core enzyme in pyrimidine nucleotide synthesis, blocking the synthesis of DNA and disrupting RNA processing [66]. Resistance to 5-FU is a major obstacle to successful treatment and identifying its underlying molecular mechanisms is one of the major challenges for creating new opportunities for LARC treatment.…”
Section: Mirnas As Potential Therapeutic Targets In 5-fluorouracil-bamentioning
confidence: 99%
“…The restoration of miR-375-3p levels enhanced 5-FU sensitivity and induced cell apoptosis and cell cycle arrest, inhibiting cell growth, migration, and invasion in vitro. Therefore, targeting miR-375-3p seems to be an effective method for modulating and enhancing 5-FU antitumor effects [66].…”
Section: Mirnas As Potential Therapeutic Targets In 5-fluorouracil-bamentioning
confidence: 99%
“…Subsequently, the cells were cultured with 5 μg/mL 5-FU for 48 hrs, and then their apoptosis was determined via an Annexin V-FITC Kit (Huijia Biotechnology Co., Ltd., Xiamen, China) under the kit instructions. The treated cells were prepared into 1×10 6 cells/mL cell suspension, followed by incubation with Annexin V-FITC and propidium iodide in the dark. Finally, the cells were determined using a CyFlow Cube6 flow cytometer (Jiyuan Biotechnology Co., Ltd., Guangzhou, China).…”
Section: Determination Of Apoptosis and Cell Cyclementioning
confidence: 99%
“…5 They play a key regulatory role in the development and progression of tumor cells, and also take a crucial part in the tumor biosynthesis, growth, and drug resistance. 6 Recent studies have found that miRNA expression can enhance the antitumor effect of 5-FU on tumor cells. 7 According to reports, miR-145 acts as a tumor suppressor in various tumors.…”
Section: Introductionmentioning
confidence: 99%